Prevalence, awareness, treatment and control of hypertension in Indonesian adults aged ≥40 years: Findings from the Indonesia Family Life Survey (IFLS) - Hussain, M.; Al Mamun, A.; Reid, C.; Huxley, Rachel (Public Library of Science, 2016)
Objective: Hypertension is the major driver of the cardiovascular epidemic facing Indonesia in the 21st century. Understanding the socioeconomic inequalities associated with hypertension is essential for designing effective intervention strategies. The aim of the current study was to use sub-nationally representative survey data to examine socio-demographic inequalities in the prevalence, diagnosis and management of hypertension in Indonesian adults. Methods: We investigated factors associated with hypertension prevalence, diagnosis, treatment and control using data on self-reported diagnosis and treatment, and blood pressure measurements, collected from 9755 respondents aged 40 years and up in the 2007 Indonesian Family Life Survey (IFLS 4). Results: Age-standardized prevalence of hypertension among the study participants was 47.8% (95% CI: 46.8, 48.9), of which almost 70% were undiagnosed. Hypertension was significantly higher in women than men (52.3% versus 43.1%, p-value<0.001). Prevalence of hypertension increased significantly with ageing (Pfor trend <0.001). Over 91% (men: 92.1%, women: 90.0%) of hypertension cases were uncontrolled. Gender, education and socioeconomic status had differential impact on the diagnosis of hypertension and in receiving treatment. Conclusions: Overall, less than a third were aware of their hypertension and a quarter of those on medication had their blood pressure effectively controlled. Men and those of younger age were more vulnerable to have undiagnosed and untreated hypertension. Substantial effort should be given to improve awareness about the condition and making provision for early diagnosis and treatment.